Pengenalan Augmented Reality Pada Komunitas Belajar SMP Negeri 23 Seluma - Dewi Suranti; Juju Jumadi; Abdussalam Al Akbar; Ridho Rahman Kurnianto; Defri Wiranata (Jurnal Dehasen Mengabdi, 2024)
The development of information technology has introduced various innovations in education, one of which is the use of Augmented Reality (AR) as an interactive learning medium. This community service activity aims to provide teachers and students with an understanding of the concept and utilization of Augmented Reality in the learning process at SMP Negeri 23 Seluma. The implementation method was carried out through a workshop consisting of preparation, implementation, and evaluation stages. During the implementation stage, participants were given material about the concept of Augmented Reality and practical training using AR applications such as AR-Kids and Assemblr Edu. The results show that participants gained increased knowledge about Augmented Reality technology and were able to use AR applications in learning activities. This activity is expected to improve teachers’ competencies and encourage the use of innovative technology in the learning process to create more engaging and interactive learning experiences.